Multifunctional behaviour in B-site disordered double perovskite EuPrCoMnO6. (23rd June 2022) - Alam, Mohd; Ghosh, Labanya; Majumder, Supriyo; Singh, Prajyoti; Kumar, Satya Vijay; Dixit, Srishti; Kumar, Dheeraj; Anand, Khyati; Kumari, Seema; Ghosh, A K; Choudhary, R J; Chatterjee, Sandip
Abstract: We report magnetic, transport, dielectric, and complex impedance of polycrystalline double perovskite EuPrCoMnO6 which crystallizes in disordered orthorhombic phase with space group Pnma. The DC magnetization shows two successive ferromagnetic transitions around 146 K and 138 K. The temperature and magnetic field variation of DC-susceptibility suggest the existence of Griffith phase and spontaneous exchange bias. AC susceptibility measurement shows a glassy dynamic behaviour near ferromagnetic transition. Further, a re-entrant glassy dynamic state is seen at a low temperature around 40 K. Temperature-dependent resistivity shows semiconducting/insulating nature, which gets increased under the application of magnetic field, showing positive magnetoresistance. The dielectric study shows usual frequency-dependent step-like behaviour with a colossal dielectric constant near room temperature. The complex impedance study shows both grain and grain boundary contribute to the electrical properties. The observed properties suggest the material can be used for spintronic devices and high dielectric applications.